PELATIHAN KERJA SEBAGAI STRATEGI PENINGKATAN PRODUKTIVITAS TENAGA KERJA - Tia Charolin; Ayu Dewi Mayasari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: This study analyzes the implementation of the job training program conducted by the Manpower and Transmigration Office of West Kutai Regency in improving local labor productivity. Increasing labor productivity is a challenge in regional manpower development, particularly in areas with limited skills and employment opportunities. This study aims to analyze the implementation of strategies to increase labor productivity through job training programs and to identify the inhibiting factors. Employing a descriptive qualitative approach, data were collected through interviews, observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana. The theoretical framework used is Wheelen and Hunger's strategy implementation, comprising three indicators: program, budget, and procedures. The results show that strategy implementation has not been optimal. For the program indicator, training was executed as planned and improved participants' skills, yet post-training follow-up remains inadequate. For the budget indicator, management is sound, but financial constraints limit program coverage. For procedures, implementation relies on partner institutions' internal SOPs because official SOPs for job training are unavailable. Inhibiting factors are both internal and external. The findings indicate that the main factors affecting the effectiveness of strategy implementation in West Kutai Regency are budget limitations, suboptimal post-training monitoring, limited access to competency certification, and the absence of official SOPs for the job training sector.Keywords: Strategy Implementation; Labor Productivity; Job Training.